The expert report and its reliability check at the intermediate stage: a scientific acceptability model - Mejia Mendo, Hector Humberto (2024)
The expert report for its formal admission as evidence in the intermediate stage of the criminal proceeding, according to the rules set forth in the procedural code of 2004, does not require the verification of the epistemological quality of its instruments, methods and results, since it is only required to be relevant, useful and conducive. This situation allows that even when in their elaboration they use theories contrary to those established by the scientific community, they are admitted for their performance in trial, ignoring the damage (overvaluation of scientific knowledge) that they cause in the performance of the judges at the time of resolving their cases, which potentially affect the wrong convictions or acquittals to which the judicial system is exposed. The objective of this article is limited to examine the doctrinal and theoretical possibilities for the adoption of the scientific admissibility control model of the expert reports in the intermediate stage, in which the quality and scientific reliability are analyzed for their admission, in order to obtain their proposed resolution capacity for the case; concluding in the possibility of incorporating this model to the Peruvian criminal procedural system, together with the criteria of procedural admissibility established in the norm.